Machine Learning and Artificial Intelligence Faux News Detection: A Review Analysis (Journal of Informatics Education and Research, 2026)
Faux news has been spreading in the recent years and has become an issue in this digital age. However, there is a light at the end of the tunnel. Faux news is still doing well thus, it has varied socio-political and economic consequences with the spread of social media and online news outlets. Faux news has been spreading in the recent years and has become an issue in this digital age. However, there is a light at the end of the tunnel. Faux news is also thriving leading to various socio-political and economic consequences as a result of the spread of the social media and online news outlets. With the development of the field of Machine Learning (ML) and Artificial Intelligence (AI), new tools to detect and regulate faux news have been developed as we still fight the proliferation of fake news. It is claimed that automated conversational AI agents have taken the form of talking to people with negative views and instructing them to become open-minded. Such discussions have been effective at lowering the number of people who follow conspiracy theories, which is a demonstration of the ability of AI to rekindle the brains of those who fall victim to fake news. Development of defraud detection software, such as the Reality Defender, is another move in the correct direction in the effort to detect original and AI-edited videos using real-time analysis. The idea behind such services is to identify discrepancies in the visual experience and inform the user in the quickest time possible to ensure high-level deceit is reduced and digital information platforms are secure. AI usage also assists in keeping external influences actors on the social media platform under control, enhancing the efficiency of the detection of disinformation efforts. Practising deception, artificial intelligence systems ensure the preservation of trust by the users in the information and communication systems.The need to solve these problems of faux news has increased the creation of new solutions that incorporate AI and ML technologies outside of the traditional paradigms of misinformation detection and alleviation.